Replication of hepatitis C virus in cell culture - Rybalko, S.L.; Porva, Yu.I.; Alekseenko, I.P.; Diadiun, S.T.; Zavelevych, M.P.; Borovykov, V.M.; Popova, L.A.; Fedorchenko, D.B. (Інститут молекулярної біології і генетики НАН України, 2009)
The technique for replicating hepatitis C virus (HCV) in cell culture has been modified and the susceptibility of the cells of various origin to HCV upon their infection with HCV-containing sera has been compared. The viral load on the fifth day post-infection has been assessed by reverse transcriptase polymerase chain reaction technique. The highest infection and replication efficacy have been found in cells of rat Gasser’s ganglion neurinoma. The peculiar features of the mitotic index and the anomalous forms of the mitosis have been studied in HCV-infected cells. The data presented may be used as a basis for the experimental model of HCV infection in vitro suitable for studying the effects of antiviral drugs on the infection caused by the cytopathogenic variant of HCV.